Noncommunicable Disease Risk Factors Among Adolescent Boys and Girls in Bangladesh: Evidence From a National Survey - Urmy, Nushrat Jahan (Osong Public Health Res Perspect, 2020)
OBJECTIVES: To assess the prevalence of noncommunicable disease (NCD) risk factors and the factors associated with the coexistence of multiple risk factors (≥ 2 risk factors) among adolescent boys and girls in Bangladesh. METHODS: Data on selected NCD risk factors collected from face to face interviews of 4,907 boys and 4,865 girls in the national Nutrition Surveillance round 2018–2019, was used. Descriptive analysis and multivariable logistic regression were performed. RESULTS: The prevalence of insufficient fruit and vegetable intake, inadequate physical activity, tobacco use, and being overweight/obese was 90.72%, 29.03%, 4.57%, and 6.04%, respectively among boys; and 94.32%, 50.33%, 0.43%, and 8.03%, respectively among girls. Multiple risk factors were present among 34.87% of boys and 51.74% of girls. Younger age (p < 0.001), non-slum urban (p < 0.001) and slum residence (p < 0.001), higher paternal education (p = 0.001), and depression (p < 0.001) were associated with the coexistence of multiple risk factors in both boys and girls. Additionally, higher maternal education (p < 0.001) and richest wealth quintile (p = 0.023) were associated with the coexistence of multiple risk factors in girls. CONCLUSION: The government should integrate specific services into the existing health and non-health programs which are aimed at reducing the burden of NCD risk factors.